In Contempt - Darden, Christopher A. and Walter, Jess (New York Regan Books, 1996)
"For more than a year, Christopher Darden argued passionately and tirelessly, giving voice to the victims in the O.J. Simpson murder trial. But few people knew that he was fighting a deeper, more insidious battle - against racism that came from all sides. When the case was over and O.J. Simpson was set free, the disheartened prosecutor bore the anguish and disillusionment of millions of Americans. He also carried wounds that perhaps no other black person has ever felt as deeply. Now, out of the sensational frenzy of the "trial of the century" comes a haunting and poignant memoir of duty, justice, and the constant, powerful undertow of American bigotry." "Christopher Darden's In Contempt is an unflinching look at a justice system kidnapped by a racist cop, shameless defense lawyers, a starstruck judge, and a dysfunctional jury. It shows what the television cameras couldn't: behind-the-scenes meetings where Darden tried to determine whether detective Mark Fuhrman was telling the truth about his racist views; deteriorating relationships between the defense and prosecution teams, with taunting, baiting, and a pushing match between Darden and Simpson; and a judge who let the case get out of control while he collected hourglasses from fans and invited celebrities into his chambers." "Darden is stunningly candid about his own performance - including the brash decision to put the gloves on Simpson - and details the inner workings of the largest prosecution team in California history. He also recounts the strong relationship forged between himself and Marcia Clark, who was exhausted by the pressures of a bitter ex-husband and demeaning treatment from other lawyers and the judge."--Jacket.
Include Illustrations
Keywords: Biography